Efeitos de um programa de exercício aeróbio intradialítico em portadores de doença renal crônica: ensaio clínico randomizado - CRUZ, Lucas Gonçalves (2016)
Patients with chronic kidney disease (CKD-PPT) have a high prevalence of overweight and obesity, chronic low-grade inflammation (ICBG) and reduced aerobic capacity. This study aimed to investigate the effect of intradialitic aerobic training on anthropometric, metabolic syndrome (MS), inflammation, renal function and physical performance in PP-DRC. Thirty PP-CKD treated with hemodialysis (HD) were randomly assigned to aerobic training (TA, n = 15) and control (CON, n = 15) groups. The TA group underwent twelve weeks of intervention with intradialitic aerobic exercise and the CON group was asked to keep daily habits. In the moments before (pre) and after (post) 12 weeks of intervention participants underwent anthropometric measurements, blood samples for biochemical and immunological analysis, measurement index Kt / V and physical performance test. ANOVAs revealed an interaction effect to reduce body mass index (BMI), waist circumference (WC), systolic blood pressure (SBP), diastolic blood pressure (DBP), glycated hemoglobin (HbA1c), IL-1b, IL-6 , IL-8 and TNF-a and increased HDL-c, IL-10 and distance covered in a 6-minute walk test (6MWT). There was a reduction of 26.7% of cases of MS in the AT group at the end of the experiment. We conclude that twelve weeks of aerobic training intradialitic positively alter anthropometric measurements, four of the five components of MS, inflammation and physical performance of PP-CKD treated with HD.